Neurobiology of spinal nociception: new concepts - Sandkühler, Jürgen (Towards the neurobiology of chronic pain, 1996)
The classical concept of acute nociception well describes many features of acute nociception but fails to explain phenomena seen during prolonged, chronic pain states. For example, chronic pain may outlast the period of nociceptor discharge and may persist when discharge rates in higher order neurons have declined. The classical concept also provides no explanation for plastic changes in nociception that may last for hours, days, or longer. The concepts on spinal processing of nociceptive information under pathophysiological conditions are described in this chapter. Recent work has largely extended the concepts about the nociceptive system. The powerful endogenous anti-nociceptive mechanisms have been identified that may depress nociceptive discharges by segmental, propriospinal and supraspinal, and descending systems. The chapter presents new hypotheses that have been proposed about the mechanisms underlying chronicity of pain and discusses the solution for indicators for spinal nociception under pathophysiological conditions. The neurophysiological mechanisms underlying plastic changes of nociception and which neuromediators are involved in the spinal cord are explained in the chapter. The possible molecular mechanisms leading to long-term changes of spinal nociception is also described.
Online 29 February 2008
Gesehen am 03.05.2021